TMPR-scheme for reliably broadcast messages among peer processes. (1st January 2011) - Aikebaier, Ailixier; Enokido, Tomoya; Takizawa, Makoto
Nowadays information systems are being shifted to distributed architectures. The peer-to-peer (P2P) model as a fully distributed system, is composed of peer processes (peers). Here, peers have to efficiently and flexibly make an agreement on one common value which satisfies an agreement condition. In the agreement protocol, each peer has to deliver values to all the peers in a group. We take advantage of the multipoint relaying (MPR) mechanism to efficiently broadcast messages. Here, if a peer which forwards messages to other peers is faulty, the peers cannot receive messages. In this paper, we newly discuss a trustworthiness-based broadcast (TBB) algorithm where only the trustworthy peers forward messages. That is, untrustworthy peers, i.e., peers prone to faults and malicious behaviours do not forward messages. Here, the transmission fault implied by faulty peers can be reduced. We evaluate the TBB algorithm in terms of the number of messages compared with the pure flooding and MPR algorithms.